Road Traffic Injuries Among Patients Who Attended the Accident and Emergency Unit of the University of Malaya Medical Centre of the University of Malaya Medical Centre, Kuala Lumpur - Moe, H. (Faculty of Medicine, University of Malaya, 2008)
A retrospective cross-sectional study of injury patients who attended the Accident and Emergency Unit was conducted at the University of Malaya Medical Centre. Demographic data with regards to age, sex, race, occupation and the relevant data such as type of accident, type of injury sustained and also severity seen during the month of January 2005 were selected retrospectively from medical record. The objectives were to review road trafÞ c accidents and their severity of injuries among the patients.